Molecular, morphological, and toxinological characterizations of an Argentinean strain of Halamphora coffeaeformis with potential biotechnological applications - Sala, Silvia Estela (2021)
Diatoms are a diverse group of unicellular microalgae with broad biotechnological and industrial applications. Recent studies have revealed that some species from the genus Halamphora accumulate high quantities of lipids, which make them potentially suitable for biodiesel production. However, due to their high phenotypic plasticity, molecular phylogenetic and ultrastructural analyses are usually needed for precise species identification, which in turn is crucial to define the cultivation strategies to obtain the main target compound. Moreover, the use of diatoms for nutrition, health, and aquaculture requires prior analysis of the potential toxicity of the selected species. In the present study we provide a detailed morphological, molecular, and toxinological evaluations of an Argentinian strain of Halamphora coffeaeformis with potential as feedstock of triglycerides adequate for biodiesel as well as a source of high-value metabolite production, in order to confirm its identification and to define the safety of its biomass in relation to domoic acid production. The obtained results will strengthen and diversify the use of this species in the microalgal market.